Retrospective analysis of a gabapentin high dose taper compared to lorazepam in acute inpatient alcohol withdrawal. (4th July 2019) - Morrison, Matthew; Udeh, Elizabeth; Burak, Michelle
ABSTRACT: Background : Benzodiazepines have remained the standard of care for alcohol withdrawal syndrome; however, they have numerous unfavorable physiologic effects. Gabapentin has limited data to support a benefit in reducing benzodiazepine usage in alcohol withdrawal syndrome. Objectives : Evaluate the association of an institutional guideline and order set for alcohol withdrawal that incorporates high dose gabapentin tapers in acutely withdrawing patients. Methods : This retrospective study evaluated patients experiencing acute alcohol withdrawal. Two time periods were evaluated: a pre-protocol group assessed outcomes prior to implementation of a gabapentin backbone taper-based guideline (PRE-implementation), and a post-protocol group assessed post-guideline and order set introduction (POST-implementation). A total of 100 patients (50 PRE-implementation and 50 POST-implementation; 84% male, 16% female) were included in the analysis. Results : There was a significant difference in the median daily lorazepam usage in the PRE-implementation versus POST-implementation groups (9.48 [5.58–28.46] vs 6.52 [3.84–11.65] mg, P = 0.024) with a reduction observed in the POST-implementation group. There was also a significant difference in the mean hospital length of stay (LOS) in the PRE-implementation versus POST-implementation groups (9.92 ± 7.33 vs 7.04 ± 4.59 days, P = 0.021) in favor of the POST-implementation group. There was no difference in the number of rapid responses called, median intensive care unit (ICU) LOS, median number of days the patient was confusion assessment method for the ICU (CAM-ICU) positive or number of transfers to a higher level of care. Conclusions : Implementation of an institutional guideline and order set for alcohol withdrawal incorporating high dose gabapentin tapers was associated with a decreased median daily lorazepam use as well as hospital LOS; however, retrospective design and inherent limitations require larger prospective trials to validate results.